Adipose stem cell-derived osteoblasts sustain the functionality of endothelial progenitors from the mononuclear fraction of umbilical cord blood - Pirraco, Rogério (2013)
Vascularization is the most pressing issue in tissue engineering (TE) since ensuring that engineered constructs are adequately perfused after in vivo transplantation is essential for the construct’s survival. The combination of endothelial cells with current TE strategies seems the most promising approach but doubts persist as to which type of endothelial cells to use. Umbilical cord blood (UCB) cells have been suggested as a possible source of endothelial progenitors. Osteoblasts obtained from human adiposederived stem cells (hASCs) were co-cultured with the mononuclear fraction of human UCB for 7 and 21 days on carrageenan membranes. The expression of vWF and CD31, and the DiI-AcLDL uptake ability allowed detection of the presence of endothelial and monocytic lineages cells in the co-culture for all culture times. In addition, the molecular expression of CD31 and VE-cadherin increased after 21 days of coculture. The functionality of the system was assessed after transplantation in nude mice. Although an inflammatory response developed, blood vessels with cells positive for human CD31 were detected around the membranes. Furthermore, the number of blood vessels in the vicinity of the implants increased when cells from the mononuclear fraction of UCB were present in the transplants compared to transplants with only hASC-derived osteoblasts. These results show how endothelial progenitors present in the mononuclear fraction of UCB can be sustained by hASC-derived osteoblast co-culture and contribute to angiogenesis even in an in vivo setting of inflammatory response.